Abstracts - Lucio-Villegas, Emilio; Coimbra, Maria de Nazaré; Marques, Anabela; Martins, Alcina de Oliveira; Espinoza, Oscar; Guajardo, Dante; González Fiegehen, Luis; Loyola Campos, Javier; Grau, Eduardo; Balça, Ângela; Fonseca, Maria Adelina; Conceição, Cristina; et al. (Revista Lusófona de Educação, 2012)
Tradução, para a língua inglesa, dos resumos dos artigos publicados nesta edição.